Malaysia's 2004 General Elections: spectacular victory, continuing tensions - Mohamad, Marzuki (University of the Philippines, 2004)

(untitled)
The new Malaysian Prime Minister, Abdullah Ahmad Badawi, after approximately five months in office, led the ruling coalitionBarisan Nasional (National Front [BN]) into the countrys eleventh general elections in March 2004. The BN won spectacularly. The electoral success has been attributed as much to Abdullahs reform initiatives, which included war against graft in public and private sectors, efforts to improve public delivery system and continued commitment to growth-oriented economic policies, as to his own clean image. Further, his pronouncement of Islam Hadhari (Civilizational Islam), a progressive Islam suited to the modern times, counterbalanced the espousal of a theocratic Islamic state agenda by the opposition, Parti Islam SeMalaysia (Pan-Malaysian Islamic Party [PAS]). This struck a chord with the majority Malay/Muslim voters and led to the impressive electoral performance of the United Malays National Organization (UMNO) in Malay-majority constituencies, which seemed to spell an end to the Malay cultural revolt against the dominant Malay party caused by the sacking, arrest and imprisonment of former Deputy Prime Minister Anwar Ibrahim. The spectacular victory, however, belied continuing tensions in Malaysian politics where the fault lines are being drawn less along narrow ethnic struggle, than between contending discourses of democracy, religious identity and economic development. The election results seem to reinforce politics beyond ethnicity which has been unfolding since the 1990s.